Stress Levels and High School Adolescents Coping Mechanism during the Covid-19 Pandemic - Mustika Sajida Maharani; Mustikasari Mustikasari (Jurnal Keperawatan Padjadjaran, 2021)
Background: Adolescents are prone to psychological disorders due to their personal nature that they cannot accept changes. It is further exacerbated by the Covid-19 pandemic situation which requires all activities to be carried out online from home. Purpose: This study aims to determine the relationship between stress levels and coping mechanism in high school adolescents during the Covid-19 pandemic in Halim Jakarta. Methods: Research design is a cross sectional used for adolescents aged 15-19 years at SMA Negeri 67 Jakarta and SMA Angkasa 1. 342 samples were selected by using the quota sampling method. The measurement of stress levels is done by distributing the Perceived Stress Scale (PSS) questionnaire, while the coping mechanism uses the Brief Cope questionnaire. The research results include the results of univariate analysis and bivariate analysis with the Chi Square test. Results: The results of this study showed that there was a relationship between stress levels and coping mechanism (p value 0.017), dysfunctional coping strategies (p value 0.000) in high school adolescents during the Covid-19 pandemic. Furthermore, there is no relationship between stress levels and Emotion Focused Strategies (p value 0.703), and Problem Focused Strategies (p value 0.816) in high school adolescents during the Covid-19 pandemic. The female adolescents are more dominant than male adolescents. More respondents from class XII majoring in science are from SMA Negeri 67 Jakarta. There are still teenagers with severe stress during the Covid-19 pandemic. There is a relationhip between stress levels with coping mechanism and dysfunctional coping strategies. But the stress level has no relationship with Emotion Focused Strategies and Problem Focused Strategies. Conclusion: The results of this study are expected to improve mental health services through routine mental health screening and providing counselling related to stress management in adolescents. Adolescents are also expected to solve problems by optimizing the use of coping mechanism (Emotion Focused Strategies, Problem Focused Strategies) appropriately and avoiding the use of dysfunctional coping strategies.